Persepsi Guru PAI BP dalam Menegakkan Disiplin Siswa (Tinjauan Kasus Guru Supriyani) di SMA Muhammadiyah 1 Purwokerto: Perceptions of Islamic Religious Education Teachers in Upholding Student Discipline (Case Review of Teacher Supriyani) at Muhammadiyah 1 High School, Purwokerto - Fikriar Devandri; Ellen Prima (ITScience (Information Technology and Science), 2025)
Enforcing discipline in schools is an important aspect in shaping character and a conducive learning environment. However, in practice, teachers often face a dilemma when disciplinary actions result in parental reporting, as seen in the case of Teacher Supriyani at SDN 4 Baito, Southeast Sulawesi. This study aims to describe the perceptions of Islamic Religious Education and Character Education (PAI BP) teachers regarding the enforcement of student discipline, particularly in the context of teacher reporting cases, with a focus on SMA Muhammadiyah 1 Purwokerto. The research method used is qualitative with a phenomenological approach, which seeks to understand the subjective experiences of PAI BP teachers in implementing discipline and the challenges they face. Data were obtained through in-depth interviews, observation, and documentation. The results show that PAI BP teachers view discipline as a manifestation of Islamic values ??that guide students to be obedient, responsible, and have good morals. Discipline is implemented in a persuasive, humanistic, and educative manner through habituation to worship, role models, and open communication with parents. Teachers emphasized the importance of documentation and coordination with the school to avoid misunderstandings that could lead to legal conflicts. They also recognized the need to strengthen legal protection and legal literacy for teachers to better prepare them for potential reporting. This study concluded that enforcing discipline grounded in Islamic values not only shapes students' religious character but also strengthens collaborative relationships among teachers, students, and parents. These findings contribute to the development of an educational discipline model that aligns with teachers' professional ethics and the demands of modern educational law.